New born care practices among mothers who delivered at home or institutions in Barhathwa VDC of Sarlahi district. - Jha, Narendra Kumar (2008)
SUMMARY: Government of Nepal has formulated the " National neonatal health strategy" with goal to improve the health and survival of newborn babies in country and the strategic objectives focus on increasing the adoption of healthy newborn care practices, reducing the prevailing harmful practices and strengthening neonatal health services. Besides the efforts taken, improvements in child survival over the past 25 years, there is still virtually no effective health care for newborns in developing countries. Newborn mortality can be significantly reduced through improved household practices and use of community based health services. Health status of a family, community and newborn is largely determined by health practices. Therefore, this study aims to describe the newborn care practices among mothers who delivered at home or institutions and its determinants in Barhathwa Village Development Committee of Sarlahi district. The cross-sectional explorative study was carried out in Barhathwa Village Development Committee of sarlahi district. Total of 224 samples were used for study purposes which included all nine wards of the Village Development Committee. Pretested questionnaires were used in the survey and in-depth interview was conducted with private practioner, mother in-law, and Primary Health Center in-charge, Auxiliary Nurse Midwife, Traditional Birth Attendants and Female Community Health Volunteers. Data were collected by researcher himself and with the help of enumerators from 10th -25th Shrawan, 2065. The collected data were entered in the statistical package for social science (SPSS) and analyzed with both descriptive and inferential statistics. Chi square test was done to see the association between newborn care practices and different background characteristic. Association was seen at 95 percent confidence interval (95% Confidence Interval). Qualitative data was analyzed by content analysis. Mean age of the respondent was 23.5 years. Most of the respondents were Janjati and Dalit. Among them, 97 percent of the respondents were Hindu. Among the respondents percent were illiterates. About 57 percent of delivery was conducted at home and rest it different health institutions. More than 45.5 percent of the deliveries were conducted by trained health workers. Five essential newborn care namely cleanliness during delivery, cord care, thermal care, breast feeding and eye care were analyzed to see the association with background characteristics. More than 85 percent of the deliveries were conducted with good cleanliness practices during delivery. Regarding cord care, only 32.1 percent of the newborn received good clean cord care and good thermal care for the newborn was only 0.9 percent. Most of the mother (46.9%) used firewood along with clothes to warm the room which was considered to be the bad practice. Breast feeding practice was found good. Colostrums feeding practice was found good (99.1%). Nearly 30 percent of the newborn received good eye care. Less than one-fourth of respondent maintained good newborn care practices. Mothers with age group 15-24 were 1.4 times more likely to have good practice on newborn care. Regarding health worker, trained health worker was about two times more likely to have good newborn care practices. This study highlights the deficiencies in newborn care. Both hospital practices and traditional home care neglected the basic principles of newborn care practices (Cleanliness, cord car, thermal care, early initiation of breast feeding and eye care). The presence of trained health person even should be encouraged. Some high-risk newborn care practices were still present, need to address through culturally acceptable community-based program.